Electrochemical template synthesis of Ni–Cu bilayer hollow microtubes for green hydrogen production through electrocatalytic reforming of ethanol. (12th May 2022) - Dmitriev, D.S.; Tenevich, M.I.; Popkov, V.I.
Abstract: This article is devoted to the investigation of the processes occurring at the synthesis of Ni–Cu hollow tubes (NC-HT) and their application as an electrocatalyst in the hydrogen evolution reaction from water-ethanol solution. The reactions at the electrochemical reduction of CuO to Cu and during the electrodeposition of nickel were investigated by chronopotentiometry. Depending on the thickness of the nickel layer, morphology (SEM) and chemical composition (EDX-mapping, XRD) of tubes, as well as electrocatalytic activity (CVA, ECSA, TOF, and stability tests) were studied. The synthesized materials have a structure with a high electrochemically active surface area (ECSA) from 1.38 to 3.50 m 2 g -1, which makes it possible to fulfill low activation overpotential values equal to −86 and −250 mV at 10 and 50 mAcm −2 after 100 cycles. The stability test results demonstrate the overpotential values −160, −183, −265 mV for NC-HT15, NC-HT30, and NC-HT60, respectively, after 24 h examinations. Graphical abstract: Image 1 Highlights: A new method of synthesizing hollow bilayer nickel-copper microtubules is proposed. Thin layers of nickel increase the ECSA of the copper precursor by 1.5 times. The overpotential of HER on hollow microtubules are improved from −280 to −86 mV.